Oko poetki. Uwagi o twórczości Ewy Elżbiety Nowakowskiej - Rabizo-Birek, Magdalena (Poznańskie Studia Polonistyczne. Seria Literacka, 2018)
The article describes the work of the poet from Cracow,the author of short stories, essayist and translator – Ewa Elżbieta Nowakowska. Her poems were situated on the map of Polish literature among the “born in the seventies”, in the strand of “emboldened imagination” poetry, in the background of “Cracow school of poetry”, in a circle of women’s poetry. The main themes of her work: religion, the world of nature, history, culture and were presented by selecting relevant examples of her poems. In the conclusion, it was hypothesized that the varied work of the poet combines with the interest in perception and cognition, for what is available for the sense of sight as well as for what is hidden: transcendence and the mystery of being, expressed in the poet’s works by the broad metaphor of “the eye”.